2013
DOI: 10.5455/jasa.20130331052157
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Fish Species Diversity, Abundance and Diets of Selected Predator Fish in Insukamini Dam, Zimbabwe

Abstract: A total of 8 fish species (n=465) were caught by gill nets from December 2009 to May 2010 to investigate fish ecology in Insukamini dam. The species were identified as: Serranochromis robustus (n=18), Micropterus salmoides (n=36), Clarias gariepinus (n=72), Oreochromis mortimeri (n=192), Oreochromis macrochir (n=27), Tilapia rendalli (57), Tilapia sparrmanii (n=6) and Oreochromis niloticus (n=57). The largest catches of fish were recorded in February (n=210). O. mortimeri reported the most abundant fish specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The ichthyofaunal was fairly diverse, although the species richness was low, which is a general characteristic of small reservoirs (Marshall & Maes, 1994). Similar reservoirs in Zimbabwe studied by Dalu et al (2013) and Dube and Kamusoko (2013) where eight species were observed in both Malilangwe Reservoir and Insukamini Dam, which have a similar surface area as Chitsuwa Reservoir. A diverse aquatic community in a reservoir provides a greater probability of maintaining ecosystem conditions when it is subjected to perturbations (Yachi & Loreau, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…The ichthyofaunal was fairly diverse, although the species richness was low, which is a general characteristic of small reservoirs (Marshall & Maes, 1994). Similar reservoirs in Zimbabwe studied by Dalu et al (2013) and Dube and Kamusoko (2013) where eight species were observed in both Malilangwe Reservoir and Insukamini Dam, which have a similar surface area as Chitsuwa Reservoir. A diverse aquatic community in a reservoir provides a greater probability of maintaining ecosystem conditions when it is subjected to perturbations (Yachi & Loreau, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…Data on fish studies in Zimbabwe is often limited to large dams and/ or lakes, such as Lake Chivero and Lake Kariba (Karenge & Kolding, 1995;Brendonck et al, 2003;Mudzimu, 2013;Muzvondiwa et al, 2013;Chifamba & Videler, 2014). Other fish diversity studies have also been done in other water bodies in the country, namely Insukamini dam and Malilalngwe reservoir (Dube & Kamusoko, 2013;Dalu et al, 2013). However, despite its size, there is no documented study on the fish communities in Tugwi Mukosi, the largest inland dam in Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%